2019
DOI: 10.1016/j.physbeh.2019.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Human behaviour at the origin of maternal effects on offspring behaviour in laying hens (Gallus gallus domesticus)

Abstract: Regular visual presence of humans is known to reduce chickens' human-generated stress responses. Here we questioned whether, more than mere visual presence, human behaviour affects laying hen behaviour and subsequently their offspring's behaviour. We hypothesized that human behaviour triggers maternal effects via variations in yolk hormone levels. For five consecutive weeks, two groups of hens were exposed to the same durations of human presence (30 min twice a day, five days a week) but the behaviour of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…In their lifetimes, layer breeders in commercial production can produce approximately 115 female offspring 10 , meaning that their experiences c Previous research has shown that hens subjected to a moderate heat challenge for ve consecutive weeks laid eggs with higher concentrations of yolk steroid hormones (progesterone, testosterone and estradiol) and had lighter and calmer offspring than control 11 . In the Japanese quail, human behaviour during handling (predictable and gentle versus unpredictable and fast) also affected the concentration of progesterone and estradiol in yolk and on offspring social discrimination skills 12 . Likewise, Japanese quails subjected to stressful events, such as sudden movement or unpredictable noise, laid eggs with higher yolk testosterone and progesterone, and produced chicks more sensitive to social separation (i.e., vocalized more during emergence and open-eld tests) 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In their lifetimes, layer breeders in commercial production can produce approximately 115 female offspring 10 , meaning that their experiences c Previous research has shown that hens subjected to a moderate heat challenge for ve consecutive weeks laid eggs with higher concentrations of yolk steroid hormones (progesterone, testosterone and estradiol) and had lighter and calmer offspring than control 11 . In the Japanese quail, human behaviour during handling (predictable and gentle versus unpredictable and fast) also affected the concentration of progesterone and estradiol in yolk and on offspring social discrimination skills 12 . Likewise, Japanese quails subjected to stressful events, such as sudden movement or unpredictable noise, laid eggs with higher yolk testosterone and progesterone, and produced chicks more sensitive to social separation (i.e., vocalized more during emergence and open-eld tests) 13 .…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy con rms the importance of time of stress exposure and suggests that maternal effects are caused by different mechanisms over time. While stressors experienced by the pullet during development might affect her offspring primarily through epigenetics 50 , stress exposure during adulthood seems to lead to changes in concentration of egg yolk hormones, as seen in lizards 51 , quails 52,53 and laying hens 17,54 . Traditionally, maternally transferred androgens such as testosterone have been suggested as the primary mediator of these effects 19 , but research has also focused on other hormones including glucocorticoids 20 and thyroid hormones 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Edwards et al (2010) showed for laying hens that 12 min/day of visual contact with humans during rearing resulted in reduced avoidance behaviour of humans during adulthood and there was a trend for hens receiving positive handling to have a lower corticosterone response to human contact than those receiving negative handling. Visible human presence associated with predictable approach, human voice, slow movements and gentle handling for weighing, were effective in inducing habituation to humans in laying hens (Bertin et al 2019).…”
Section: In Poultrymentioning
confidence: 99%